Glyceryl trinitrate to reduce the need for manual removal of retained placenta following vaginal delivery: the GOT-IT RCT - Fiona C Denison (Health Technology Assessment, 2019)
Background: Retained placenta is associated with postpartum haemorrhage and can lead to significant maternal morbidity if untreated. The only effective treatment is the surgical procedure of manual removal of placenta, which is costly, requires skilled staff, requires an operative environment and is unpleasant for women. Small studies suggest that glyceryl trinitrate may be an effective medical alternative. Objective: To determine the clinical effectiveness and cost-effectiveness of sublingual glyceryl trinitrate spray compared with placebo in reducing the need for manual removal of placenta in women with retained placenta after vaginal delivery following the failure of current management. Design: A group-sequential randomised double-blind placebo-controlled trial with a cost-effectiveness analysis. Setting: There were 29 obstetric units in the UK involved in the study. Participants: There were 1107 women (glyceryl trinitrate group, n = 543; placebo group, n = 564) randomised between October 2014 and July 2017. Interventions: Glyceryl trinitrate spray was administered to 541 women in the intervention group, and a placebo was administered to 563 women in the control group. Main outcome measures: Four primary outcomes were defined: (1) clinical – the need for manual removal of placenta, (2) safety – measured blood loss, (3) patient sided – satisfaction with treatment and side effects and (4) economic – cost-effectiveness of both treatments using the UK NHS perspective. Secondary clinical outcomes included a > 15% decrease in haemoglobin level, time from randomisation to delivery of placenta in theatre, the need for earlier manual removal of placenta than planned, increase in heart rate or decrease in blood pressure, requirement for blood transfusion, requirement for general anaesthesia, maternal pyrexia, and sustained uterine relaxation requiring additional uterotonics. Results: No difference was observed between the glyceryl trinitrate group and the control group for the placenta remaining undelivered within 15 minutes of study treatment (93.3% vs. 92%; odds ratio 1.01, 95% confidence interval 0.98 to 1.04; p = 0.393). There was no difference in blood loss of > 1000 ml between the glyceryl trinitrate group and the control group (22.2% vs. 15.5%; odds ratio 1.14, 95% confidence interval 0.88 to 1.48; p = 0.314). Palpitations were more common in the glyceryl trinitrate group than in the control group after taking the study drug (9.8% vs. 4.0%; odds ratio 2.60, 95% confidence interval 1.40 to 4.84; p = 0.003). There was no difference in any other measures of patient satisfaction between the groups. There was no difference in costs to the health service between groups (mean difference £55.30, 95% confidence interval –£199.20 to £309.79). Secondary outcomes revealed that a fall in systolic or diastolic blood pressure, or an increase in heart rate, was more common in the glyceryl trinitrate group than in the control group (odds ratio 4.9, 95% confidence interval 3.7 to 6.4; p < 0.001). The need for a blood transfusion was also more common in the glyceryl trinitrate group than in the control group (odds ratio 1.53, 95% confidence interval 1.04 to 2.25; p = 0.033). Conclusions: Glyceryl trinitrate spray did not increase the delivery of retained placenta within 15 minutes of administration when compared with the placebo, and was not cost-effective for medical management of retained placenta. More participants reported palpitations and required a blood transfusion in the glyceryl trinitrate group. Further research into alternative methods of medical management of retained placenta is required. Trial registration: Current Controlled Trials ISRCTN88609453. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 23, No. 70. See the NIHR Journals Library website for further project information.